Penilaian Pelajar SMP Di Kota Yogyakarta Terhadap Pictorial Health Warning (PHW) - Citra Denali; Zahroh Shaluhiyah; Kusyogo Cahyo (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2017)
Background: Based on a national data of proportion of domestics aged ≥ 10 year old related to their smoking behaviour, Yogyakarta is 14th province with highest number of active smokers with a rate of 21,2% every day. The purpose of this research is to analyze factors influencing students of junior high schools (SMP) in Yogyakarta regarding their assessment of PHW.Method: This research is a quantitative researh supported by qualitative data. The quantitative data were obtained by a cross sectional method, while the qualitative ones by case study approach. The samples were 403students who are in seventh grade at several SMPs in Yogyakarta.Informant of indepth interview were 2 teachers SMPs, and 10 students who are in seventh grade at several SMPs in Yogyakarta.Results: The results of this research show us that 49,1% of respondens have a negative assessment of PHW. The factors contributing to the assessment of SMP students in Yogyakarta were: exposure of PHW, with ρ value of 0,0001 (ρ < 0,05) and OR/Exp (B) of 16,610; knowledge of smoking with ρ value of 0,024 (ρ < 0,05) and OR/Exp (B) of 2,041; and age, with ρ value of 0,029 (ρ < 0,05) and OR/Exp (B) of 1,808. Indepth interview shows that PHW has not been able to make a smoker (SMP student) have assessment of PHW related to them intention to quit smoking. Key Words: PHW, Assessment, Junior High School Students, Cigarette